ANALYSIS OF THE POLYMERIC MARKET AND DIRECTIONS OF INCREASING THE ACTIVITY OF ITS PARTICIPANTS - Данилюк, Микола Олексійович; Семотюк, Лілія Романівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
This article deals with the review of the problem questions concerning the reduction of the activity and the decrease of the profit of the enterprises in the field of chemistry; the analysis of manufacturing and consuming of polymers in Ukraine for the previous year; the variety of the prices for polymeric raw material and the consequences of such changes for manufactures; the defining of directions for strengthening the activity of market.